Floods, food security, and coping strategies: Evidence from Afghanistan - Hamid R. Oskorouchi; Alfonso Sousa-Poza (Agricultural Economics, 2021)
In this paper, we assess the long-term effect of floods on food security (as measured by calorie and micronutrient consumption) by applying an instrumental variable approach to data from the Afghanistan National Risk and Vulnerability Assessment survey. To identify the determinants of this effect, we also estimate how floods affect per capita yearly household income and poverty status. We find that exposure to flooding during a 12-month period decreased daily calorie consumption by approximately 60~kcal while increasing the probability of iron, vitamin A, and vitamin C deficiency by 11, 12, and 27 percentage points, respectively. Controlling for price shocks and income only marginally reduces this flood effect on food security, suggesting that impaired livelihoods (rather than price hikes) are its primary driver. We further determine that exposure to this natural disaster decreases income by about 3% and makes flood-affected households about 3 percentage points more likely to be poor. Lastly, we show that experience of floods is strongly and significantly associated with lower diet quality and quantity, and with engaging in consumption smoothing coping strategies, such as buying food on credit and taking loans. These findings underscore the serious direct impact of floods on both diet and effective behavioral responses to such shocks while emphasizing the need for targeted micronutrient supplementation in disaster relief and food aid measures even after the period of natural disaster emergency.
Keywords: 330; Afghanistan; coping strategies; floods; food security; nutrition; instrumental variables